Gender typical patterns and the link between alexithymia, dyadic coping and psychological symptoms. (July 2016) - Gabriel, Barbara; Untas, Aurélie; Lavner, Justin A.; Koleck, Michèle; Luminet, Olivier
Abstract: Prior research has identified associations between alexithymia, psychological symptoms, marital functioning and life satisfaction. However, less is known about the specific dynamics in the interplay of these associations, and other research suggests that such associations may differ depending on gender. The goal of this study is to investigate gender specific associations between alexithymia, symptoms of anxiety/depression, life satisfaction, and dyadic coping in a sample of 112 heterosexual couples. Using path analyses and extended applications of the actor–partner-independence model (APIM), results revealed significant associations between alexithymia, dyadic coping, and symptoms of anxiety/depression, as well as between dyadic coping and life satisfaction for women and for men. For women, the association between symptoms of anxiety/depression and dyadic coping was mediated by alexithymia. For men the association between alexithymia and dyadic coping was mediated by anxiety/depression. The study highlights the interplay between alexithymia, symptoms of anxiety/depression, life satisfaction, and dyadic coping, and suggests that men and women may show different patterns of association. Highlights: Alexithymia, psychological symptoms, and dyadic coping are significantly correlated. Alexithymia mediates the link between psychological symptoms and coping for women. Psychological symptoms mediate the link between alexithymia and coping for men.